Bioengineering applications for hearing restoration: emerging biologically inspired and biointegrated designs. (December 2021) - Brant, Jason A; Adewole, Dayo O; Vitale, Flavia; Cullen, Daniel K
Abstract : Cochlear implantation has become the standard of care for hearing loss not amenable to amplification by bypassing the structures of the cochlea and stimulating the spiral ganglion neurons directly. Since the first single channel electrodes were implanted, significant advancements have been made: multi-channel arrays are now standard, they are softer to avoid damage to the cochlea and pre-curved to better position the electrode array adjacent to the nerve, and surgical and stimulation techniques have helped to conform to the anatomy and physiology of the cochlea. However, even with these advances the experience does not approach that of normal hearing. In order to make significant advances in performance, the next generation of implants will require novel interface technology. Advances in regenerative techniques, optogenetics, piezoelectric materials, and bioengineered living scaffolds hold the promise for the next generation of implantable hearing devices, and hope for the restoration of natural hearing.